Exhibits in Libraries: A Practical Guide - Brown, Mary E.; Power, Rebecca (McFarland & Co., 2006)
"Library exhibits can inspire and educate, stimulate an interest that can be explored in a book, or attract visitors who otherwise wouldn't stop by. Displays are an opportunity to put a creative foot forward or help patrons navigate the facility. This "how-to" includes everything a librarian needs to know to put on an exhibit"–Provided by publisher.
Keywords: Handbooks; manuals; etc; Library exhibits; dept.ils; faculty_collection

The Pediatric Nurse's Survival Guide - Rebeschi, Lisa M.; Brown, Mary H. (Thomson Delmar Learning, 2007)
Keywords: Handbooks; manuals; etc; Pediatric nursing; dept.nur; faculty_collection